2020
DOI: 10.1155/2020/7208081
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acupuncture on Intraocular Pressure in Glaucoma Patients: A Single‐Blinded, Randomized, Controlled Trial

Abstract: Glaucoma is characterized by the degeneration of retinal ganglion cells that cause progressive optic neuropathy, finally resulting in changes to the optic nerve head. Lowering intraocular pressure (IOP) is the only method proven for treating glaucoma. Several studies have discovered that acupuncture can reduce IOP and also increase ocular perfusion and ocular blood flow. Therefore, the present study investigated the effect of acupuncture on IOP in glaucoma patients. We conducted a single-blinded, randomized, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Studies have shown [6,7] that the imbalance of aqueous humor circulation is an important factor in the pathogenesis of OHT. Acupuncture can regulate the botanic nerve function, improve aqueous humor circulation and ocular blood perfusion, and directly reduce the aqueous humor flow and intraocular pressure through the long-term accumulation of distal and proximal points.…”
Section: Discussmentioning
confidence: 99%
“…Studies have shown [6,7] that the imbalance of aqueous humor circulation is an important factor in the pathogenesis of OHT. Acupuncture can regulate the botanic nerve function, improve aqueous humor circulation and ocular blood perfusion, and directly reduce the aqueous humor flow and intraocular pressure through the long-term accumulation of distal and proximal points.…”
Section: Discussmentioning
confidence: 99%
“…Research has shown that acupuncture reduces IOP and increases retrobulbar blood flow. 3,4 The mechanism by which acupuncture reduces IOP is unclear. According to Chu et al, 5 endogenous opioids are detectable in the aqueous humor of the eye, along with their receptors, and are involved in the reduction of noradrenaline and dopamine levels in response to EA; EA-induced IOP reduction is blocked by naloxone.…”
Section: Commentmentioning
confidence: 99%
“…The pulmonary side effects are pneumothorax and asthma. The inter-vention could even turn fatal by infections such as hepatitis B [64][65][66][67][68].…”
Section: Adverse Effectsmentioning
confidence: 99%